Works by Andrii Levytskyi for the “Homage à Trois” Project (Barcelona, Spain) - Lamonova, O. (Народна творчість та етнологія, 2024)
Andrii Levytskyi is a well-known Kyivan graphic artist and a recognized master of gravure printing (intaglio). The artist has been participating regularly in the “Homage à trois” (Tribute to Three) project, which takes place in Barcelona (Spain) on the initiative of the Duana de les Arts – AIDA International Association – since 2021. Only masters of graphic art can participate in the project. It should commemorate three literary figures on the occasion of their birthday anniversaries, and the artists should choose at least two of the three proposed personalities. Intaglio 2021, satisfying the conditions of the project, at the same time continues seamlessly the themes and motifs peculiar to Andrii Levytskyi’s heritage in general. The poem about a Henna Tree (Jean Lafontaine) is somewhat unexpected and paradoxical, but naturally connected with the artist’s favorite images of trees. In The Player, the themes of confrontation, game, and rivalry are developed. They arise, in particular, in the intaglio Motus Animi Continuus (2021). Three works of 2022, made in the computer design technique, are distinguished by a bright and at the same time elegant color solution. The artist is inspired by themes of the theater and, widely, carnival culture (Molière’s Mask), and Japanese art (IchiyōHiguchi’s Stream). The work for the anniversary of the legendary German romantic Novalis (Ask Baron: Is Religion the Opium of the Peoples) is especially unexpected. In 2023, Andrii Levytskyi returned to the intaglio technique again and at the same time abandoned color. The works dedicated to Federico García Lorca (At Five O’clock in the Afternoon) and Wisława Szymborska, winner of the Nobel Prize (Cat in an Empty Apartment), are the artist’s reflections on the theme of death, while the work Dream. My Ántonia (based on the novel by Willa Cather) softens their tragical essence. The Ukrainian artist’s works dedicated to Molière, Novalis, and Willa Cather have been nominated and awarded by the organizers of “Homage à trois”. Taking part in international artistic projects, and even more so winning in them, Ukrainian artists contribute actively to the creation of a positive image of the state. After all, the culture of Ukraine consists not only of the historical heritage but also of the works of modern masters. Андрій Левицький – відомий київський графік, визнаний майстер глибокого друку (інталіо). Від 2021 року митець регулярно бере участь у проєкті «Homage à trois» («Данина трьом»), який здійснюється в м. Барселоні (Іспанія) з ініціативи Міжнародної асоціації Duana de les Arts – AIDA. Учасниками проєкту можуть бути тільки майстри графічного мистецтва. Проєкт має вшанувати пам’ять трьох літературних діячів з нагоди річниць їхнього народження, причому з трьох запропонованих персоналій художники мають обрати щонайменше дві. Інталіо 2021 року, задовольняючи умови проєкту, водночас органічно продовжують теми й мотиви, характерні для доробку Андрія Левицького загалом. «Поема про хінне дерево (Жан Лафонтен)» дещо несподівано та парадоксально, але природно пов’язана з улюбленими митцем зображеннями дерев. «Гравець» розвиває теми протистояння, гри, суперництва, які також виникають, зокрема, в інталіо «Motus Animi Continuus» (2021). Три роботи 2022 року, виконані в техніці комп’ютерного дизайну, відзначаються яскравим і разом з тим елегантним колористичним вирішенням. Художник надихається темами театру й ширше – карнавальної культури («Маски Мольєра»), мистецтвом Японії («Потік Ітійо Хігуті»). Особливо ж несподіваним є твір до ювілею легендарного німецького романтика Новаліса («Спитаю у Барона: релігія – опіум для народу?»). У 2023 році Андрій Левицький знов-таки повертається до техінки інталіо й воднораз відмовляється від кольоровості. Твори, присвячені Федеріко Гарсіа Лорці («О п’ятій годині пополудні») та Віславі Шимборській, лауреатці Нобелівської премії («Кіт у порожній квартирі»), є роздумами художника над темою смерті, тоді як робота «Сон. Моя Антонія» (за романом Вілли Катер) пом’якшує їхній трагізм. Роботи українського художника, присвячені Мольєру, Новалісу та Віллі Катер, були номіновані та нагороджені організаторами «Homage à trois». Беручи участь у міжнародних мистецьких проєктах, а тим паче перемагаючи в них, вітчизняні художники активно сприяють створенню позитивного іміджу держави. Адже культура України складається не лише з історичної спадщини, але й із творів сучасних майстрів.